Patient-reported quality of life outcomes following treatment for oral cancer. Issue 3 (March 2018) - Breeze, J.; Rennie, A.; Dawson, D.; Tipper, J.; Rehman, K.-U.; Grew, N.; Pigadas, N.
Abstract: Patient-reported quality of life (QoL) outcomes have the potential to assist clinicians in providing individually tailored treatment decisions. QoL assessments were collected prospectively for 168 consecutive patients treated for oral cancer between 1 January 2010 and 31 December 2014 using the University of Washington Quality of Life Questionnaire. Patients were followed up for 18 months post-treatment. Sub-group analyses were performed using paired t -tests and analysis of variance (ANOVA) to compare the effects of adjunctive chemoradiotherapy, type of bone resection, and methods of soft and hard tissue flap reconstruction. The greatest statistically significant reduction in QoL for all oral cavity sub-sites was found following the treatment of floor of mouth tumours (−18.9%, P  = 0.018). Laser excision for matched patient cohorts resulted in improved resultant QoL compared to other excision techniques ( P  = 0.0002). No significant difference in QoL was found when radial forearm and anterolateral thigh flaps were matched, or when fibula and scapula flaps were matched. These findings support the use of laser excision and the avoidance of postoperative radiotherapy if curative intent and survival outcomes are maintained.